2014
DOI: 10.2106/jbjs.l.01625
|View full text |Cite
|
Sign up to set email alerts
|

Fretting and Corrosion in Modular-Neck Total Hip Arthroplasty Femoral Stems

Abstract: The ABG II dual modular hip system is associated with a high rate of early failure secondary to fretting and corrosion at the femoral neck-stem taper. The component has subsequently been recalled and is no longer in use. Surgeons using modular hip systems with a titanium stem and cobalt-chromium neck should be vigilant about annual follow-up with radiographs, and use of MRIs as indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(57 citation statements)
references
References 23 publications
3
52
0
2
Order By: Relevance
“…Unique to Stryker, both the Rejuvenate and ABG II stems are made from a proprietary TMZF alloy. It has been suggested that the alloyed metals may be more susceptible to corrosion when mixed with a cobalt-chrome implant compared to single element metals [1,14]. Other modular stems with titanium stems and cobalt-chrome modular necks may be at less risk for MACC on account of their metallurgy.…”
Section: Discussionmentioning
confidence: 99%
“…Unique to Stryker, both the Rejuvenate and ABG II stems are made from a proprietary TMZF alloy. It has been suggested that the alloyed metals may be more susceptible to corrosion when mixed with a cobalt-chrome implant compared to single element metals [1,14]. Other modular stems with titanium stems and cobalt-chrome modular necks may be at less risk for MACC on account of their metallurgy.…”
Section: Discussionmentioning
confidence: 99%
“…However the size of the clinical impact of corrosion in relation to implant failure is unclear. Visual evidence of corrosion has been observed at the stem-cement interface of cemented stems [13,14], the modular neck-stem junction [9,15], the modular stem-head junction [7,11] and the interface between the shell and liner of modular cups. The current study reports retrieval findings of the backside of the modular cup liner in the largest series of retrieved modular cups to date; we found very high agreement between the visual grading of components by two independent examiners, suggesting this is a reliable method of assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Avtorji so zato predvsem pri bolnikih z večjim ITM svetovali uporabo izmenljivih vratov iz kobaltovih zlitin, ki imajo boljšo odpornost na korozijo freting, odlikuje pa jih tudi večja trdnost, višji modul elastičnosti, večja odpornost na abrazijo in manjša hitrost širjenja razpok. Žal se je kombinacija kobalt-kromovih izmenljivih vratov in debel iz titanove zlitine pokazala za problematično, saj so avtorji opažali erozijo kalkarja stegnenice, tvorbo psevdotumorjev in dejansko pospešeno korozijo freting (20,21). Prav lokalni toksičnosti kobaltovih ionov, sproščenih zaradi dodatne galvanske korozije na stiku izmenljivih vratov in debel endoproteze mo-dela Rejuvenate ameriškega proizvajalca Stryker, so pripisali odgovornost za kar 86 % revizijskih operacij, ki so bile pri bolnikih potrebne povprečno 4 leta po vstavitvi tega modela primarne endoproteze (22).…”
Section: Razpravljanjeunclassified